Intellectual Property Protection in China in the Cases of Outsourcing and own Manufacturing - Cao, Qing; Ketolainen, Mari (fi=Turun yliopisto|en=University of Turku|, 2013)
The intellectual property (IP) environment in China is still very immature. There are several problems in legal, political, economic, social-cultural, competitive and labor environment which have hindered IP legal enforcement. Under such circumstances, IP misappropriation is a major concern especially for foreign small and medium-sized enterprises (SMEs) doing business in China. These circumstances require foreign companies, no matter whether they are multinational corporations (MNCs) or SMEs and have own manufacturing in China or not, to take strong IP actions. Therefore, the purpose of this study is to discuss how IP can be protected in China in the case of outsourcing and in the case of own manufacturing. The comparison will consider the process of outsourcing and own manufacturing consisting two stages: preparation stage and operation stage. In order to clarify the conceptual arguments, two illustrative case studies were studied. The case data bases on two semi-structured interviews of the managing directors, field notes and archival data. The findings propose that attention in IP protection should be given to following issues: integrating IP strategy into the company’s business strategy, protecting the most critical knowledge, regarding IP steps as a whole in the protection mechanism and making IP strategy as proactive as possible. The major difference between outsourcing and own manufacturing in IP protection is in the operation stage. Besides, the findings also provide managerial advice on IP protection, e.g. foreign managers should be prepared for IP risks in China, they should establish an own IP protection mechanism which matches the company’s situation and they should consider IP protection as an on-going process.